DEVELOPMENT OF RAINING RAINBOW SCIENCE GAME MEDIA TO FACILITATE CHILDREN'S SCIENCE PROCESS SKILLS AT 5-6 YEARS OF AGE - Edi Hendri Mulyana; Sumardi Sumardi; Gigin Famela (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2022)
This research is motivated by the gap that occurs that the quality of introductory science learning, especially the lack of using the right media because it rarely involves children in the process of science and scientific attitudes of science so it only refers to introducing science concepts that are not in accordance with the characteristics of science learning. Learning media, especially science game media as an alternative to be used in the learning process to facilitate children's science process skills so that children have the opportunity to develop science process skills. But in reality, teachers are limited in providing and using science game media. Because of these limitations, science is dominated by the lecture method so learning is still teacher-centered. Thus the purpose of this research is to develop science game media to facilitate science process skills in children aged 5-6 years. The method in this study uses a development-based approach, namely the EDR model by Mc.Kenney & Reeves. The results of research and media development products show that it is very feasible to use in the learning process.